Derecho a la información y democracia en el marco de la globalización neoliberal: bibliotecas, archivos y medios de comunicación de masas - López López, Pedro (Revista General de Información y Documentación, 2003)
The article deals with the importance of the right to information for participation in democracy, a right exercised mainly through mass communications media but in which libraries and archives are also concerned. The consideration of information as a commodity and the treatment of public services as such constitute a threat to the citizen’s information rights and, consequently, to deterioration in the quality of the democracy.